2021
DOI: 10.3390/insects12111038
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Pest Management for Stored Grain: Potential Natural Biological Control by a Parasitoid Wasp Community

Abstract: Insect contamination of stored grain is a major concern for the grain industry. Phosphine is currently the standard fumigant used to control insect pests in stored grain. However, some species and populations of insects that infest stored grain exhibit resistance to this fumigant and consumers are concerned about pesticide residues. Therefore, alternative methods of effective pest control are needed to partially or completely replace the use of phosphine. There is growing interest in biological control via par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It has already been applied to reducing the population of Ceratitis capitata in mangoes (Wong et al, 1991; Sanchez et al, 2016) [22,18] . Bactrocera dorsalis (Hendel) (Vargas et al, 2012) [20] , Anastrepha obliqua (Macquart), and Anastrepha ludens (Loew) (Montoya et al, 2000) [15] , and it proposed as a potential natural biological control (Harush et al, 2021) [11] . The investigation results showed that the natural enemies of fruit flies in the orchard were abundant (Fig.…”
Section: Results and Discussion Natural Enemy Composition Of Fruit Fl...mentioning
confidence: 99%
“…It has already been applied to reducing the population of Ceratitis capitata in mangoes (Wong et al, 1991; Sanchez et al, 2016) [22,18] . Bactrocera dorsalis (Hendel) (Vargas et al, 2012) [20] , Anastrepha obliqua (Macquart), and Anastrepha ludens (Loew) (Montoya et al, 2000) [15] , and it proposed as a potential natural biological control (Harush et al, 2021) [11] . The investigation results showed that the natural enemies of fruit flies in the orchard were abundant (Fig.…”
Section: Results and Discussion Natural Enemy Composition Of Fruit Fl...mentioning
confidence: 99%
“…In comparison, biological control using natural enemies presents a safer and more biorational approach. Currently, parasitoid wasps from Pteromalidae, Bethylidae, Braconidae and Ichneumonidae have been reported as natural enemies of many important stored product pests, and several species have been sensibly utilized in the control of insect pests in storehouses 6 8 . Parasitoids suppress host immunity by injecting virulence factors including venom during oviposition, and the progeny consume and eventually kill the hosts, effectively, sustainably and safely controlling the host population 9 , 10 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Warehouses are generally fumigated with phosphine once per year (Vidan et al 2020). The pests support a community of several species of naturally occurring parasitoid wasps (Harush et al 2021). Based on local economic parameters (Supp Table 1 [online only]), and local insecticide efficiency of 99%, the EIL (Eq.…”
Section: Developing Eils Ets and Dts To Control Grain Beetles In Whea...mentioning
confidence: 99%